Europejskie regulacje prawne dotyczące funkcjonowania sztucznej inteligencji - Chyc, Paweł (PRAWO i WIĘŹ, 2025)
The development of new technologies, especially artificial intelligence, creates enormous opportunities for humanity on the way to further progress and development. Nowadays, no one is surprised by the fact that robots work much more efficiently than humans, and the resources of the Internet are many times greater than human memory. Artificial intelligence will also inevitably enter the everyday life of the modern world, and there is no need to fear that the development of computer intelligence will soon surpass the potential of the human mind. However, already at this stage it is necessary to distinguish digital international law by outlining the ethical and legal framework for the operation of artificial intelligence systems. Without a doubt, such a framework must take into account human rights, data protection, the rule of law, protection of intellectual property, and principles of liability for damage caused by the actions of computer intelligence. The current European achievements (within the Council of Europe and the EU) in the field of regulation of initial standards for the principles of functioning of systems based on artificial intelligence are pioneering on a global scale and for this reason it is worth making a synthetic analysis of them. This is also the aim of this study.